PENGARUH PEMBERIAN UMPAN BALIK TERHADAP KESALAHAN SISWA DALAM MENYELESAIKAN OPERASI HITUNG BENTUK ALJABAR - Rahayu, Siti (JURNAL e-DuMath, 2016)
The research is aims to determine the effect of feedback on studentsâ mistake in completing the algebra arithmetic operation. The effect can be seen by the average difference in studentsâ mistake in completing the algebra arithmetic operation between the given feedback and are not given feedback. The population was all of the second grade students at SMP Negeri 1 Adiluwih in the academic year 2015- 2016. The samples of the research were taken by using the cluster random sampling technique. The research instrument used was a test in the form of description consists of four items. Data acquisition is done by testing with data analysis techniques using U-test (Mann-Whitney U test) because the data is not normally distributed. The result of the research can be concluded that the provision of feedback can influence the students mistakes in completing the algebra arithmetic operation. The effect can be seen by the average difference in students mistakes in completing the algebra arithmetic operation between classes given feedback and classes are not given feedback. Keywords : feedback, students mistakes, algebra arithmetic operation